HRM practices, leadership styles and customer satisfaction: mediating role of employee performance - Salahat, Mahmoud A. M. (2017)
The primary purpose of this study is to investigate the effect of human resource management practices and leadership styles on customer satisfaction in the Palestinian insurance sector through the mediating role of employee performance. Empirical evidence to support the importance of customer satisfaction and what constitutes high levels of customer satisfaction is still lacking in the Palestinian context. This research framework, based on the resource-based view theory of the firm, aimed at finding out whether factors such as human resource management (HRM) practices, leadership styles, and employee performance have significant influences on customer satisfaction. Nine hypotheses, based on past research and underlying theory, were developed to test the relationships. The study sample was taken from employees of the insurance sector in Palestine, who have direct dealing with customers. The sample consisted of 358 participants selected through a systematic random process. Of the questionnaires posted, 269 were returned of which 258 were found usable, constituting a 72% response rate. The data was analyzed using the Partial Least Square (PLS). The findings indicated that HRM practices had an indirect relationship with customer satisfaction. Similarly, transactional leadership style and transformational leadership style showed indirect relationships with customer satisfaction. The findings also revealed that HRM practices and transactional leadership style and transformational leadership style had significant and positive relationships with employee performance. Finally, the results indicated that employee performance had a significant and positive relationship with customer satisfaction while also mediating the relationship between HRM practices and leadership styles respectively and customer satisfaction. The study concludes with discussions on theoretical and practical contributions, the study limitations, and suggestions for future research